Technical Efficiency Analysis of Health Expenditure Allocation in the Mataraman Region, East Java Province - Wibawa, Wahyu Aditama Putra Mukti; Prasasti, Karari Budi; Mauliddah, Nurul Laili (Universitas Gorontalo, 2025)
This study analyzes the technical efficiency of health Expenditure Allocation in the Mataraman Region. The method employed in this research is Data Envelopment Analysis (DEA). The data used are panel data, covering 12 regencies/cities within the Mataraman area. The aim of this study is to assess whether the available funds have been utilized optimally to improve health services and indicators, such as life expectancy, the Human Development Index (HDI), and the number of births assisted by medical personnel. The results indicate that not all regions have been able to utilize their health budgets efficiently. Some areas have managed their funds effectively, while others still exhibit inefficiencies in budget use. These findings are important as a basis for evaluation and policy improvement, so that future health budgets can have a greater and more equitable impact on the overall well-being of communities across East Java. The analysis results indicate that only Kediri City, Madiun City, and Blitar City consistently achieved perfect efficiency each year. In contrast, most regencies experienced inefficiencies, showing a declining trend in efficiency values over the years despite having large budget allocations.